Video modelling to improve hand dexterity in students with learning disabilities : special education teachers' perspectives - Nurbieta Abd Aziz,; Masne Kadar,; Dzalani Harun,; Hanif Farhan Mohd Rasdi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Proficient hand dexterity (HD) may help students with learning disabilities (LDs) perform various hand tasks efficiently. Video modelling (VM) is a strategy that uses a model to improve desired skills. However, the limited study focuses on VM to improve HD among students with LDs. Therefore, this study explores VM implementation in the learning and teaching process to improve the HD of students with LDs. Five Special Education (SE) teachers who taught the Hand Manipulative Component lessons in two different states were purposefully selected and invited to participate in this study. A one-to-one interview was conducted with individual SE teachers. The interview sessions were audio-recorded and transcribed verbatim, and the data was analysed through thematic analysis. Rigorous approaches were performed to ensure the findings' trustworthiness, such as triangulation, member checking, and an audit trail. Four key themes emerged: conventional learning and teaching methods, challenges faced by students with LDs in improving HD, and the advantages of implementing VM in learning and teaching to improve HD and develop a video module. This study suggests SE teachers can implement VM in their learning and teaching processes to improve the HD performance of students with LDs. This current study concludes that VM can be a supportive strategy in the teaching process to improve HD performance among students with LDs.